STRONG FANS, WEAK CAMPAIGNS: SOCIAL MEDIA AND DUTERTE IN THE 2016 PHILIPPINE ELECTION - Sinpeng, Aim; Gueorguiev, Dimitar; Arugay, Aries A. (Journal of East Asian studies, 2020)
The 2016 presidential contest is widely considered as the first “social media election” in the Philippines. At the same time, it remains unclear if or how social media helped Rodrigo Duterte mobilize voters to gain victory. There are three main social media campaigning models: broadcast, grassroots, and self-actualizing. Analysis of twenty million activities and 39,942 randomly sampled comments across the official Facebook pages of key presidential candidates supports the grassroots model as Duterte's profile was the most engaged, even if Duterte himself was not actively engaged. Such inconsistencies raise the prospect that Duterte's online prominance was fabricated by paid trolls and fake accounts. Instead, our analysis suggests that Duterte's digital fanbase was, at least in part, a reflection of offline, grassroots political support. In particular, data from an original survey of 621 respondents suggests that Duterte supporters were not only aggressive in their support for Duterte online, they were also more committed to him offline as well. These findings add to a growing literature on social media and politics that seeks to understand the broader ecosystem of online political discourse, rather than focusing on the actions and strategies of political campaigns. They also underscore the fine line between fabricated support and genuine political fervor.